Analisis Theory Of Planned Behavior Untuk Mengetahui Minat Nasabah Melakukan Gadai Emas Di Bank Syariah - Alisa Sri Nur Komala Wulan Sari; Purnama Putra (At-Tamwil: Journal of Islamic Economics and Finance, 2022)
This study aims to determine the effect of the components in Theory of Planned Behavior on customer interest in pawning gold in Islamic banks, as well as analyzing the suitability of strategies used by Islamic banks with customer needs and desires. The sample used was 100 customers as the object of research. Data management in this study uses the SPSS Statistics 21 application as a tool to analyze data, by performing test analysis techniques research instrument through validity test and reliability test, classical assumption test and multiple linear regression test interest. While the perceived behavioral control variable has a positive but not significant effect on interest. The results of the F-test of attitudes toward behavior, subjective norms and perceived behavioral control have a positive and significant effect simultaneously on interest. The result of the coefficient of determination test (R2) is 0.587, which means that the contribution of the independent variables (attitude towards behavior, subjective norms, perceived behavioral control) affects the dependent variable (interest) by 58.7% and the remaining 41.3% is influenced by variables outside the model. The results of this study also show that the strategy used by Bank BJB Syariah Pondok Gede Sub-Branch Office is in accordance with the needs and desires of customers.